The Animal in Man ─ An Image Pattern in Frank Norris’ Mcteague - Godwin Yao Gaaku; Felix Mawudor Vorvor; David Ako Odoi (Universitas Sanata Dharma, 2023)
Every man possesses an animal instinct that lingers beneath the surface, waiting for an appropriate time to manifest. In Frank Norris’ McTeague, some characters degenerate to the level of the animal, displaying brutality and striving like predators for survival. This study sought to investigate the animal metaphor as an image pattern in McTeague. The study used textual analysis as a design to analyse, interpret and evaluate McTeague. The study concluded that Joseph Le Conte’s theory of Evolution and Cesare Lombroso’s theory of criminology influenced the writing of McTeague. Thus, there is extensive use of the animal metaphor as an image pattern through the characters in the novel: McTeague, Trina, Marcus and Zerkow. They are metaphorically hustled up and down the evolutionary ladder between the levels of the animal and the human. Consequently, these characters degenerate to metaphorical animals and constitute an image pattern in the novel. When things are normal, their animal instincts are not only concealed but also tamed and only come out when things become abnormal. The study further established that the animal instinct is there in every human; hence, everyone must be conscious of this animal instinct and learn to control it in times of abnormality. The study recommends that future researchers investigate how this animal instinct can be tamed in man when faced with instinctual forces.